# Pvhs Algebra 2 Mid-term

26 Questions | Total Attempts: 180  Settings  This test contains information from the PVHS Algebra 2 Coursework, from sections 1-4

Related Topics
• 1.
Solving Equations: X+B = C Solve for x:x + 3 = -1
• A.

X = -5

• B.

X = -8

• C.

X = -4

• D.

X = 9

• 2.
Solving Equations: X+B = C Solve for x:x + 7 = 9
• A.

X = 1

• B.

X = 2

• C.

X = 3

• D.

X = 8

• 3.
Solving Equations: AX = C Solve for x:8x = 4
• A.

X = 1/2

• B.

X = 0

• C.

X = 3/2

• D.

X = 3/8

• 4.
Solving Equations: AX = C Solve for x:-6x = -2
• A.

X = -7/3

• B.

X = -5/2

• C.

X = 1/5

• D.

X = 1/3

• 5.
Solving Equations: AX+B = C Solve for x:19.74x - 1 = -357.8
• A.

X = 121990/4537

• B.

X = 3587/40

• C.

X = -17840/987

• D.

X = 21124/12765

• 6.
Solving Equations: AX+B = CX+D Solve for x:-16.87x - 8 = 17.99x + 618
• A.

X = 17911/1109

• B.

X = -31300/1743

• C.

X = -5341/26970

• D.

X = 3094/2007

• 7.
Solving Equations: AX+B = CX+D Solve for x:-16.84x - 57.16 = 10.1x - 264.6
• A.

X = 10372/1347

• B.

X = 1477/4353

• C.

X = -9884/1857

• D.

X = -925/27

• 8.
Interval Notation 1 Write in interval notation: <= is < and >= > infinity = ∞3 <  x  <= 9
• A.

( -5, -1 )

• B.

( 3, 9 ]

• C.

( -2, -1 )

• D.

( - infinity, 0 ) U ( 9, infinity )

• 9.
Interval Notation 1 Write in interval notation: <= is < and >= > infinity = ∞x <= 3  or  x > 8
• A.

( - infinity, -8 ) U ( 5, infinity )

• B.

[ -6, 6 ]

• C.

( - infinity, 3 ] U ( 8, infinity )

• D.

( - infinity, 3 ] U ( 9, infinity )

• 10.
Interval Notation 2 Write in set-builder notation: <= is < and >= > infinity = ∞( - infinity, -3 ]  U  ( 3, infinity )
• A.

{ x | x < -8 or x > 3 }

• B.

{ x | x < -6 or x > 8 }

• C.

{ x | x 1 }

• D.

{ x | x 3 }

• 11.
Interval Notation 2 Write in set-builder notation: <= is < and >= > infinity = ∞[ 3, 7 ]
• A.

{ x | 3

• B.

{ x | x < -5 or x >= -4 }

• C.

{ x | -1 < x

• D.

{ x | -10

• 12.
Solving Inequalities: AX+B < C Solve for x:8x - 2 > -8
• A.

X > -3/4

• B.

X > -3/10

• C.

X > -9/5

• D.

X > -7/3

• 13.
Solving Inequalities: AX+B < C Solve for x:2x - 2 > -3
• A.

X < 5/2

• B.

X > -6/5

• C.

X > -1/2

• D.

X < 1/7

• 14.
Solving Inequalities: AX+B , CX+D Solve for x:-x + 10 < -8x - 4
• A.

X > 1/11

• B.

X > 1/2

• C.

X > 11/5

• D.

X < -2

• 15.
Solving Inequalities: AX+B , CX+D Solve for x:-5x - 6 < x + 3
• A.

X > -3/2

• B.

X > 11/7

• C.

X > -4

• D.

X > 11/4

• 16.
Finding the Slope of a Line Given Two Points Find the slope of the line passing through:( 0, -9 ) and ( 7, -10 )
• A.

M = -1/7

• B.

M = -8/6 = -4/3

• C.

M = 1/17

• D.

M = -9/8

• 17.
Finding the Slope of a Line Given Two Points Find the slope of the line passing through:( 7, 9 ) and ( -8, -4 )
• A.

M = 10/-13 = -10/13

• B.

M = -3/2

• C.

M = -13/-15 = 13/15

• D.

M = 1/11

• 18.
Equation of a Line Given a Point & the Slope Find the equation of the line: with the slope m = 1 and passing through the point( -1, -8 )
• A.

-11x + 11y = -77

• B.

4x + 3y = -17

• C.

-2x + 9y = -1

• D.

X + 9y = 66

• 19.
Equation of a Line Given a Point & the Slope Find the equation of the line: with the slope m = 6 and passing through the point( 3, 3 )
• A.

3x + 8y = -83

• B.

-8x + 17y = 98

• C.

X + 2y = 12

• D.

Y = 6x - 15

• 20.
Parallel Lines Find the equation of the line that is parallel to the line: 9x - 3y = 7 and passes through the point:( -3, -1 )
• A.

X + y = -15

• B.

6x + y = 11

• C.

X + 2y = 13

• D.

-3x + y = 8

• 21.
Parallel Lines Find the equation of the line that is parallel to the line: -7x + 4y = 9 and passes through the point:( 8, 9 )
• A.

-7x + 4y = -20

• B.

-x + y = 3

• C.

X + 2y = -9

• D.

6x + 7y = 47

• 22.
Perpendicular Lines Find the equation of the line that is perpendicular to the line: -6x - 2y = -3 and passes through the point: ( -4, 7 )Find the slope by solving for y.
• A.

-10x + 7y = -2

• B.

4x + y = -27

• C.

X + 4y = 22

• D.

-x + 3y = 25

• 23.
Perpendicular Lines Find the equation of the line that is perpendicular to the line: -8x - 8y = -2 and passes through the point: ( -10, -2 )Find the slope by solving for y.
• A.

5x + 7y = 42

• B.

2x + 3y = -25

• C.

-x + y = 8

• D.

5x + 8y = -4

• 24.
Function Notation 1 x2 = x^2 Given the function: f ( x ) = -9x^2 + 2x + 7 findf ( 4 )
• A.

F ( -4 ) = 102

• B.

F ( -9 ) = 319

• C.

F ( 4 ) = -129

• D.

F ( 7 ) = -326

• 25.
Function Notation 1 x2 = x^2 Given the function: f ( x ) = -3x^2 + 4x + 3 findf ( 9 )
• A.

F ( -8 ) = -1479

• B.

F ( 9 ) = -204

• C.

F ( 1 ) = -14

• D.

F ( 9 ) = -85